The Role of Earning Per Share Target and Analyst Forecast in Shaping CEO Compensation Structures and Driving Strategic Decision Makin - Ngadi Permana (LPPM STIE Kasih Bangsa, 2024)
This research examines CEO compensation schemes by contrasting analyst expectations with earning per share (EPS) targets. The study synthesizes recent literature to investigate how various compensation systems affect management behavior, corporate governance, and financial performance. The results show that CEOs are motivated by EPS objectives to participate in earnings management strategies, which involve influencing financial outcomes to satisfy preset benchmarks. Managerial decision-making is heavily influenced by analyst projections, which motivate strategic action intended to align company performance with market expectations. The analysis underscores the governance implication, emphasizing the trade-offs between immediate financial objectives and long-term sustainability.